Developing the competence of future teachers in applying innovative pedagogical technologies through an acmeological approach - Babanazarovna, Kunnazarova Bibhikhadicha (Goodwood Publishing, 2025)
Purpose: This study aims to explore the role of the acmeological approach in shaping the functional and professional competence of future teachers, emphasizing its integration with innovative pedagogical technologies to meet the demands of 21st-century education. Research Methodology: The research employs a qualitative-descriptive method through literature review and theoretical analysis of pedagogical models. Sources include recent studies on acmeology, teacher training, and the application of digital and interactive learning technologies. Results: Findings demonstrate that the acmeological framework strengthens teacher candidates’ ability to integrate theory with practice. When combined with innovative teaching technologies such as project-based learning, problem-oriented methods, and digital platforms, the approach fosters creativity, critical thinking, adaptability, and reflective practice. These elements contribute to higher pedagogical mastery and professional identity development. Conclusions: The integration of acmeological principles and innovative pedagogical technologies creates a synergistic paradigm for teacher preparation. It not only enhances methodological flexibility but also motivates continuous self-improvement and professional responsibility, ensuring future teachers are equipped to address contemporary educational challenges. Limitations: The study is conceptual in nature, relying primarily on secondary data and theoretical frameworks. Empirical validation through longitudinal or experimental research is recommended. Contribution: The article contributes to pedagogical science by providing a structured conceptual model for teacher development that unites acmeological strategies with innovative educational technologies, offering insights for curriculum designers, educators, and policymakers.